Systemic hypertension in cats with acute kidney injury. (5th September 2017) - Cole, L.; Jepson, R.; Humm, K.
Abstract : Objective: To describe the prevalence of systemic hypertension in cats with community‐acquired acute kidney injury and investigate its relationship with disease severity. Materials and Methods: Retrospective study of cats presenting to the Queen Mother Hospital for Animals, Royal Veterinary College with acute kidney injury between 2007 and 2015. Systolic blood pressure was measured using Doppler sphygmomanometry and systemic hypertension was defined pressures ê150 mmHg. Median systolic blood pressure measurement, grade of acute kidney injury (as defined by the International Renal Interest Society), serum creatinine on admission, anuria or oliguria, length of hospitalisation, survival to discharge and six‐month survival were all recorded. Results: Forty‐six cats were included; 21/48 (48.8%) showed systemic hypertension on admission and was severe (ê180 mmHg) in 8/43 (18.6%). During the whole hospitalisation period, systemic hypertension was detected in 27/46 (58.7%) cases and severe in 13/46 (28.2%). Systemic hypertension did not appear to be statistically associated with grade of kidney injury, serum creatinine on presentation, oliguria or anuria. Clinical Significance: Systemic hypertension is common in cats with acute kidney injury but does not appear to be associated with its severity.